2004
DOI: 10.1124/dmd.32.8.775
|View full text |Cite
|
Sign up to set email alerts
|

The Main Role of Ugt1a9 in the Hepatic Metabolism of Mycophenolic Acid and the Effects of Naturally Occurring Variants

Abstract: ABSTRACT:Mycophenolic acid (MPA), a standard immunosuppressive drug, is characterized by unexplained highly variable pharmacokinetics in transplant recipients. The primary metabolic pathway of MPA is glucuronidation; however, literature reports are inconsistent and the contribution of all human UDP-glucuronosyltransferases (UGTs) has never been systematically assessed. Sixteen heterologously expressed UGTs were studied for MPA 7-O-glucuronidation and compared with liver, kidney, and intestine microsomes. For d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
167
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(180 citation statements)
references
References 15 publications
9
167
4
Order By: Relevance
“…Enzymatic activities, derived from microsomal preparations of these cell lines, are consistent with mRNA expression profiles. HT-115 and LOVO cell lines displayed high catalytic activity toward bilirubin (a specific substrate of UGT1A1) 13 and MPA (a substrate of UGT1A8 and UGT1A9) 11 (Figure 3c). Glucuronidating activity for estradiol and irinotecan's active metabolite SN-38, both conjugated by multiple UGT1A isoforms 1, 12,14,15 was also significant in these two cell lines (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymatic activities, derived from microsomal preparations of these cell lines, are consistent with mRNA expression profiles. HT-115 and LOVO cell lines displayed high catalytic activity toward bilirubin (a specific substrate of UGT1A1) 13 and MPA (a substrate of UGT1A8 and UGT1A9) 11 (Figure 3c). Glucuronidating activity for estradiol and irinotecan's active metabolite SN-38, both conjugated by multiple UGT1A isoforms 1, 12,14,15 was also significant in these two cell lines (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Physiological function of UGT1A_i2 spliced forms J Bellemare et al described 6,7,11,12 and was reported as glucuronidation rates (area or pmol min -1 mg -1 protein).…”
Section: Glucuronide Formation Was Measured By Hplc-ms/ms Asmentioning
confidence: 99%
“…UGT1A9 enzyme variant M33T, heterologously expressed in HEK293 cells, showed 1.7-fold reduced intrinsic clearance (V max /K m ) for mycophenolic acid 7-O-glucuronide (mycophenolic acid is the active metabolite of a standard immunosuppressive drug mycophenolate mofetil) [40], and 26-fold reduced intrinsic clearance for SN-38 glucuronide (SN-38 is the active metabolite of an anticancer drug irinotecan) [14]. The other UGT1A9 enzyme variant D256N, heterologously expressed in COS-1 cells, showed 22-fold reduced intrinsic clearance for SN-38 glucuronide [15].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that polymorphisms in the UGT1A9 gene result in significant alteration of the UGT enzymatic activity. Two polymorphisms, both in the promoter region of the UGT1A9 gene (C-275T>A) and (C-2152C>T), result in higher MPA glucuronidation rates [70], whereas the UGT1A9*3 (P 33M>T) polymorphism results in decreased enzyme activity and lower glucuronidation rate of MPA compared to the wild-type [71]. Clinical investigation of the effects of the UGT1A9-275T>A and -2152C>T polymorphisms in kidney transplant recipients has demonstrated that carriers of either or both polymorphisms had lower MPA area under the curve (AUC) and trough concentrations [59,60,62].…”
Section: Mycophenolic Acid (Mpa)mentioning
confidence: 99%